Activation of 5-HT1A receptor reduces abnormal emotionality in stress-maladaptive mice by alleviating decreased myelin protein in the ventral hippocampus. (December 2021) - Kurokawa, Kazuhiro; Takahashi, Kohei; Miyagawa, Kazuya; Mochida-Saito, Atsumi; Takeda, Hiroshi; Tsuji, Minoru
Abstract: We previously reported that abnormal emotionality in stress-maladaptive mice was ameliorated by chronic treatment with flesinoxan, a 5-HT1A receptor agonist. Furthermore, the maintenance of hippocampal myelination appeared to contribute to the development of stress adaptation in mice. However, the effects of 5-HT1A receptor activation on myelination under the stress-maladaptive situations and the underlying mechanisms remain unknown. In the present study, we examined using flesinoxan whether activation of 5-HT1A receptor can reduce an abnormal emotional response by acting on oligodendrocytes to preserve myelin proteins in stress-maladaptive mice. Mice were exposed to repeated restraint stress for 4 h/day for 14 days as a stress-maladaptive model. Flesinoxan was given intraperitoneally immediately after the daily exposure to restraint stress. After the final exposure to restraint stress, the emotionality of mice was evaluated by the hole-board test. The expression levels of brain-derived neurotrophic factor (BDNF), phosphorylated-extracellular signal-regulated kinase (p-ERK), phosphorylated-cAMP response element-binding protein (p-CREB), myelin-associated glycoprotein (MAG), myelin basic protein (MBP) and oligodendrocyte transcription factor 2 (olig2) in the hippocampus was assessed by western blotting. Hippocampal oligodendrogenesis were examined by immunohistochemistry. Chronic treatment with flesinoxan suppressed the decrease in head-dipping behaviors in stress-maladaptive mice in the hole-board test. Under this condition, the decreases in MAG and MBP in the hippocampus recovered with increase in BDNF, p-ERK, p-CREB, and olig2. Furthermore, hippocampal oligodendrogenesis in stress-maladaptive mice was promoted by chronic treatment with flesinoxan. These findings suggest that 5-HT1A receptor activation may promote oligodendrogenesis and myelination via an ERK/CREB/BDNF signaling pathway in the hippocampus and reduces abnormal emotionality due to maladaptation to excessive stress. Graphical abstract: Image 1 Highlights: 5-HT1A receptor agonist ameliorates abnormal emotionality in stress-maladaptive mice. 5-HT1A receptor agonist activates ERK/CREB/BDNF signaling pathway in stress-maladaptive mice. 5-HT1A receptor agonist increases MAG and MBP protein levels in stress-maladaptive mice. 5-HT1A receptor agonist promotes myelination and oligodendrogenesis in stress-maladaptive mice.